Introduction to leadership concepts and practice - Northouse, Peter G. (Los Angeles, California SAGE Publications, Inc., 2018)
The Fourth edition of Peter G. Northouse's bestselling Introduction to Leadership: Concepts and Practice provides readers with a clear overview of the complexities of practicing leadership and concrete strategies for becoming better leaders. The text is organized around key leader responsibilities such as creating a vision, establishing a constructive climate, listening to outgroup members, and overcoming obstacles. Three interactive components of every chapter - self-assessment questionnaires, observational exercises, and reflection and action worksheets - get readers actively involved in applying leadership concepts to their own lives. Grounded in leadership theory and the latest research, the fully updated, highly practical Fourth Edition includes a new chapter on how leaders can embrace diversity and inclusion, as well as new material on the dark side of leadership and a new ethical leadership style questionnaire.--Back cover.
International Student Edition.
Includes bibliographical references and index.
Keywords: Leadership